Penerapan Penerapan Teknik Brainwriting Untuk Melatih Keterampilan Menulis Karangan Ekspositori Pada Mata Kuliah Menulis II Program Studi Pendidikan Bahasa Mandarin Universitas Negeri Malang - Dini Permadi; Sawitri Retnantiti; Karina Fefi Laksana Sakti (Journal of Chinese Language and Culture Studies, 2025)
This study aims to describe the activities of Mandarin Language Education Study Program students at State University of Malang in the application of Brainwriting techniques to train expository essay writing skills and describe student responses to the application of Brainwriting techniques. This research uses a descriptive qualitative approach. The data sources in this study were 36 students of the Mandarin Language Education Study Program class of 2022 offering B. Based on the results of the research, the Brainwriting technique can help students find ideas in writing expository essays, based on ideas that have been written on group worksheets by producing vocabulary that is used as a guide in developing expository essays. The theme of this expository essay is可爱的熊猫 [kě'ài de xióngmāo](cute panda) with the title of expository essay长颈鹿 [Chángjǐnglù](giraffe). However, all groups were unable to write 500-1000 字, because based on the students' responses, the time for writing expository essays was too short at 30 minutes and the hanzi strokes in the concluding structure were too many.